2015
DOI: 10.1016/j.engstruct.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterisation of walking locomotion on rigid level surfaces using motion capture system

Abstract: a b s t r a c tLow-frequency structures, such as footbridges and long-span floors, are often sensitive to variations in dynamic loading induced by pedestrians. As a result, the design of these structures using traditional deterministic approaches is being replaced by stochastic load models that can accommodate different styles of walking. To inform development and facilitate wider implementation of the new stochastic approaches, a database of experimental data characterising both inter-and intra-subject variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Nearly twenty years ago Kerr [5] acknowledged a great inter-subject variability between amplitudes of individual footfall records. Further studies demonstrated inadequacy of the deterministic modelling approach to describe reliably the actual random nature of individual walking excitation among the human population [4,[6][7][8][9]. More recent research also showed that the Fourier modelling approach leads to significant loss of information and introduction of inaccuracies during the data reduction process [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Nearly twenty years ago Kerr [5] acknowledged a great inter-subject variability between amplitudes of individual footfall records. Further studies demonstrated inadequacy of the deterministic modelling approach to describe reliably the actual random nature of individual walking excitation among the human population [4,[6][7][8][9]. More recent research also showed that the Fourier modelling approach leads to significant loss of information and introduction of inaccuracies during the data reduction process [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…In a similar way, Carroll et al [13] reproduced the lateral GRFs induced by walking from 31 active markers and used this to analyse the pedestrian's balance when walking on a laterally oscillating deck. In [20], Dang et al used up to 27 markers to experimentally characterize the walking locomotion on rigid surfaces. For jumping and bobbing, McDonald et al [11] show that the tracked marker motion of the C7th vertebrae (C7) at the base of the neck is a good approximation of the motion of the body center of mass (BCoM).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal parameters can be grouped as: step frequency (cadence), speed, stride time, stance time, swing time, single and double support and similar. Spatial parameters, whose values change with location, are: step length, step width, foot angle, attack angle, end-of-step angle and trunk orientation [54,55,58], as shown in Figure 2. The reader is referred to [57] for more information on gait cycle.…”
Section: Spatio-temporal Gait Parametersmentioning
confidence: 99%
“…The temporal parameters are familiar to engineers, in particular step frequency and walking speed. The spatial gait parameters, however, are not fully investigated or incorporated in the context of vibration serviceability [58]. Lack of thorough studies for gait parameters may in fact result in inadequate walking force model.…”
Section: Spatio-temporal Gait Parametersmentioning
confidence: 99%
See 1 more Smart Citation